If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y(y + 7) = 42 Reorder the terms: 4y(7 + y) = 42 (7 * 4y + y * 4y) = 42 (28y + 4y2) = 42 Solving 28y + 4y2 = 42 Solving for variable 'y'. Reorder the terms: -42 + 28y + 4y2 = 42 + -42 Combine like terms: 42 + -42 = 0 -42 + 28y + 4y2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-21 + 14y + 2y2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-21 + 14y + 2y2)' equal to zero and attempt to solve: Simplifying -21 + 14y + 2y2 = 0 Solving -21 + 14y + 2y2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -10.5 + 7y + y2 = 0 Move the constant term to the right: Add '10.5' to each side of the equation. -10.5 + 7y + 10.5 + y2 = 0 + 10.5 Reorder the terms: -10.5 + 10.5 + 7y + y2 = 0 + 10.5 Combine like terms: -10.5 + 10.5 = 0.0 0.0 + 7y + y2 = 0 + 10.5 7y + y2 = 0 + 10.5 Combine like terms: 0 + 10.5 = 10.5 7y + y2 = 10.5 The y term is 7y. Take half its coefficient (3.5). Square it (12.25) and add it to both sides. Add '12.25' to each side of the equation. 7y + 12.25 + y2 = 10.5 + 12.25 Reorder the terms: 12.25 + 7y + y2 = 10.5 + 12.25 Combine like terms: 10.5 + 12.25 = 22.75 12.25 + 7y + y2 = 22.75 Factor a perfect square on the left side: (y + 3.5)(y + 3.5) = 22.75 Calculate the square root of the right side: 4.769696007 Break this problem into two subproblems by setting (y + 3.5) equal to 4.769696007 and -4.769696007.Subproblem 1
y + 3.5 = 4.769696007 Simplifying y + 3.5 = 4.769696007 Reorder the terms: 3.5 + y = 4.769696007 Solving 3.5 + y = 4.769696007 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3.5' to each side of the equation. 3.5 + -3.5 + y = 4.769696007 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + y = 4.769696007 + -3.5 y = 4.769696007 + -3.5 Combine like terms: 4.769696007 + -3.5 = 1.269696007 y = 1.269696007 Simplifying y = 1.269696007Subproblem 2
y + 3.5 = -4.769696007 Simplifying y + 3.5 = -4.769696007 Reorder the terms: 3.5 + y = -4.769696007 Solving 3.5 + y = -4.769696007 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3.5' to each side of the equation. 3.5 + -3.5 + y = -4.769696007 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + y = -4.769696007 + -3.5 y = -4.769696007 + -3.5 Combine like terms: -4.769696007 + -3.5 = -8.269696007 y = -8.269696007 Simplifying y = -8.269696007Solution
The solution to the problem is based on the solutions from the subproblems. y = {1.269696007, -8.269696007}Solution
y = {1.269696007, -8.269696007}
| 0.3(1+a)=2.1a | | 16/9x=128 | | p(x)=x^5-7x^4-2x^3+78x^2-63x-135 | | 6=(7-2x)(3-2x) | | x^2+5=16 | | 4[-8x+5]=-32x-26 | | 12-(10xn)=-28 | | -5.9a-2/3=5/6 | | -57=-19p | | -5/9-2/3=5/6 | | -6x^2=-24 | | -4x-2=-2x | | -4+4x-x=20 | | 3[1-3x]=2[-4x+7] | | 12-(10xn)=28 | | 29=n-16 | | 8-x/2=53 | | X+9+2x+6=90 | | 4x+4-x=31 | | -26=n-13 | | 1/4x+4=7 | | 3(x+3)=-3(x+1)-5 | | 2d-2+3d=38 | | -5x+18=-8x | | -2x+47=-28 | | 8x+4[4x-3]=4[6x+4]-4 | | 4/3x+2=-2 | | 7x+26=10x+8+15x | | -7x+16=x | | -5x+38=-8x+2 | | x^2+16=63 | | 6x+7y=-49 |